A New Definition of Human Suffering and Satisfaction According to the Entropy Hypothesis: End Stage Dementia and Entropy - Aminoff, Bechor Z. (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Background: The emotional and intellectual life of human beings is composed of two principal conditions: a feeling of well-being and a condition of despair, i.e. a feeling of satisfaction and enjoyment, and a state of suffering. Human suffering has received limited attention in medical education, research, and practice. Objectives: A new definition of human suffering and satisfaction according to the entropy hypothesis may facilitate comprehension of health, disease, and the aging process. Methods: A cohort study of 71 patients (28 females, 43 males), with very advanced dementia, who died in our ward during the study period. The intense suffering level of end-stage dementia patients was evaluated by the Mini-Suffering State Examination (MSSE) scale. Comparisons between the three levels of MSSE (low, intermediate, and high) with regard to demographic and clinical variables, were performed using analysis of variance (ANOVA), Kruskal Wallis non-parametric test, and Fisher’s exact test, where applicable. Results: Suffering level in end-stage dementia has a significant correlation with short survival, advancing age, more severe illness, malnutrition, the existence of decubitus ulcers, and the administration of medications. Established correlations could be explained by the enhanced level of the patient’s body entropy. Discussion: Suffering and satisfaction are functional levels of human entropy. An elevated level of human entropy is a measure of disorder, a process of ageing and torment of the patient.